Methodical bases of productive logic: practical advice (Journal of Philosophy Culture and Political Science, 2015)
The paper discusses the basic directions of creative thinking for thoseyoung people who are seriously decided to engage in such a cognitiveconstruct, which is called science. Based on a specific template culture ofproductive thinking, the authors provide practical recommendations fortheir formation. On the basis of case studies opens up the scope of theproductive logic, which is essentially different from the formal and symboliclogic in content, in which each entity engaged in scientific activitydevelops the ability to think creatively about the real.
Keywords: Productive logic; critical thinking; creative thinking; intelligence; thesis method formula.